Smart Planning in the Saga of Khoja Maimum: Applications of Principles in Planning Management Approach - Beden, Sara (Malay Literature, 2018)
This paper aims to analyze the problem solving strategies in relation to moral issues in the traditional prose of Hikayat Khoja Maimun according to the planning principles that are part of the 'management approach'; one of the methods of analysis in the world of literary criticism in our country. The method of research is qualitative, with focus on text analysis. Applying aspects of the aforementioned planning principles, four events are analyzed that have been taken from the Hikayat Khoja Maimun. The results of the analysis showed that the problem-solving strategies usedby Bayan's character to overcome problems or moral issues with regards to the character of Zainab Bibi's violation vary in terms of morality and ethic. The strategy formed is based on the use of praise and support, personal analogy technique, storytelling or saga, questions, criticism and support, attracting attention and providing advice. The variation of formation in problem-solving strategies shows that systematic and smart planning is very significant in the analysis of data besides revealing the traditional community's power of intellect and wisdom, as well as providing a detailed look at its thought. Keywords: problem solving strategies, " Hikayat Khoja Maimun ", model of planning principles, smart planning, variation, analogy